Rare case report: sclerosing epithelioid fibrosarcoma with FUS-CREB3L1 gene fusion - Wang, Tingting; Xu, Haimin; Li, Chuanying (Frontiers in Oncology, 2025)
Sclerosing epithelioid fibrosarcoma (SEF) is a rare soft tissue malignancy frequently misdiagnosed due to its overlapping immunohistochemical and molecular features with low-grade fibromyxoid sarcoma (LGFMS). We present the case of a 60-year-old male who initially presented with a mass in the left thigh four years ago, which significantly increased in size over the past year. MRI of the femur revealed a large, well-circumscribed mass in the mid and lower left thigh. Surgical excision of the tumor and associated thrombus in the ipsilateral blood vessel was performed. Histomorphological analysis confirmed a pure SEF with no myxoid stroma, aiding in its differentiation from LGFMS. Immunohistochemical staining revealed diffuse and strong MUC4 positivity, while next-generation sequencing (NGS) demonstrated molecular characteristics consistent with LGFMS, specifically FUS-CREB3L1 gene fusion. This case underscores the asynchrony between the pathological morphology and molecular features of soft tissue tumors during their development and differentiation. Although histologically low-grade, SEF typically exhibits a high rate of local recurrence and distant metastasis. We diagnosed this case as SEF and recommended an aggressive clinical treatment regimen. This report aims to raise awareness of the diagnostic challenges associated with SEF and LGFMS.